Agency Problem Handling Strategy in Shariah Bank - Rahmayati, Rahmayati; Khairunnisa, Khairunnisa (IQTISHODUNA: Jurnal Ekonomi Islam, 2023)
In the period 2018 - 2020 there were 21, 8 and 26 findings of internal fraud cases at Bank Muamalat in the GCG report. Meanwhile, in BNI Syariah there are 8 to 9 findings of internal fraud contained on the official BNI Syariah website. Sharia Bank is a banking institution that is carried out based on sharia principles. Therefore, this study outlines various problems that may cause agency problems in Islamic banks. This research uses ANP research methods to describe problems and find solutions related to Agency Problems in Islamic Banking. The main problem causing the Agency Problem is the lack of supervision on the profit-sharing financing mechanism, in line with the priority of solutions related to agency problems, namely routine supervision related to financing that has been distributed. This result was agreed upon by the speakers with a rater agreement value of W = 0.24.